2021
DOI: 10.3390/ijerph18073625
|View full text |Cite
|
Sign up to set email alerts
|

Erector Spinae Plane Block for Perioperative Analgesia after Percutaneous Nephrolithotomy

Abstract: Erector spinae plane block was recently introduced as an alternative to postoperative analgesia in surgical procedures including thoracoscopies and mastectomies. There are no clinical trials regarding erector spinae plane block in percutaneous nephrolithotomy. The aim of our study was to test the efficacy and safety of erector spinae plane block after percutaneous nephrolithotomy. We analyzed 68 patients, 34 of whom received erector spinae plane block. The average visual analogue scale score 24 h postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…For postoperative analgesics, 20 studies used morphine, 11 , 21 , 27 , 31 , 32 , 35 , 36 , 40 , 43–45 , 47 , 48 , 50 , 54 , 55 , 60 , 64 , 65 , 68 11 studies used fentanyl, 14 , 38 , 41 , 42 , 46 , 51 , 56–59 , 62 9 studies used tramadol, 23 , 28–30 , 37 , 39 , 49 , 53 , 63 5 studies used sufentanil, 12 , 22 , 24–26 4 studies used pethidine, 33 , 34 , 66 , 67 2 studies used oxycodone 10 , 52 and 1 study used nalbuphine. 61 However, the heterogeneity did not reduce by the subgroup analysis ( Figure 5 ).
Figure 5 Forest plot for subgroup analysis of the effect of ESPB on postoperative opioid consumption during the first 24 h after surgery, different type of postoperative analgesics.
…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…For postoperative analgesics, 20 studies used morphine, 11 , 21 , 27 , 31 , 32 , 35 , 36 , 40 , 43–45 , 47 , 48 , 50 , 54 , 55 , 60 , 64 , 65 , 68 11 studies used fentanyl, 14 , 38 , 41 , 42 , 46 , 51 , 56–59 , 62 9 studies used tramadol, 23 , 28–30 , 37 , 39 , 49 , 53 , 63 5 studies used sufentanil, 12 , 22 , 24–26 4 studies used pethidine, 33 , 34 , 66 , 67 2 studies used oxycodone 10 , 52 and 1 study used nalbuphine. 61 However, the heterogeneity did not reduce by the subgroup analysis ( Figure 5 ).
Figure 5 Forest plot for subgroup analysis of the effect of ESPB on postoperative opioid consumption during the first 24 h after surgery, different type of postoperative analgesics.
…”
Section: Resultsmentioning
confidence: 92%
“…Among them, 41 studies reported the incidence of PONV after surgery. 10–12 , 21–27 , 31 , 32 , 34 , 35 , 37–41 , 43–48 , 50 , 51 , 53 , 55–59 , 61–67 The results showed that compared to control group, ESPB significantly reduced the incidence of PONV (OR 0.51; 95% CI 0.43, 0.62; p<0.01; p for heterogeneity = 0.15, I 2 = 19%). ( Supplementary Figure 4 ) Because of low heterogeneity, it was unnecessary to conduct sensitivity analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations